Legal Protection for MSMEs as Borrowers in Peer-to-Peer Fintech Lending under on OJK Regulation Number 77/POJK.01/2016 - Christmas Petra Keppy; Aurora Jillena Meliala (Jurnal Ilmiah Dunia Hukum, 2025)
The development of fintech Peer-To-Peer (P2P) lending services in Indonesia has opened up faster, more flexible, and affordable access to financing for Micro, Small, And Medium Enterprises (MSMEs), but has also given rise to problems of high interest rates, over-indebtedness, and imbalances in borrower bargaining power compared to providers. This study examines the form of legal protection for MSMEs as borrowers in fintech P2P lending services based on POJK Number 77/POJK.01/2016 and the development of interest limit regulations through the AFPI code of ethics, SEOJK Number 19/SEOJK.06/2023, and POJK Number 4/2024. The method used is normative legal research with a normative juridical approach, based on analysis of laws and regulations, literature, and secondary data related to P2P lending practices. The results show that POJK 77/2016 initially only provided preventive and repressive protection based on transparency and complaint mechanisms without explicit interest limits, so it is insufficient to suppress excessive interest practices and total costs. The shift to price-based regulation through formal interest caps strengthens legal protection for MSMEs by limiting the maximum daily economic benefit and total costs, reducing the risk of predatory practices and over-leverage, while maintaining P2P lending’s role as an alternative source of financing for MSMEs.